Identification of a systemic lupus erythematosus susceptibility locus at 11p13 between PDHX and CD44 in a multiethnic study (2011)
Systemic lupus erythematosus (SLE) is considered to be the prototypic autoimmune disease, with a complex genetic architecture influenced by environmental factors. We sought to replicate a putative association at 11p13 not yet exceeding genome-wide significance (p < 5 × 10-8) identified in a genome-wide association study (GWAS). Our GWA scan identified two intergenic SNPs located between PDHX and CD44 showing suggestive evidence of association with SLE in cases of European descent (rs2732552, p = 0.004, odds ratio [OR] = 0.78; rs387619, p = 0.003, OR = 0.78). The replication cohort consisted of >15,000 subjects, including 3562 SLE cases and 3491 controls of European ancestry, 1527 cases and 1811 controls of African American (AA) descent, and 1265 cases and 1260 controls of Asian origin. We observed robust association at both rs2732552 (p = 9.03 × 10-8, OR = 0.83) and rs387619 (p = 7.7 × 10-7, OR = 0.83) in the European samples with pmeta = 1.82 × 10-9 for rs2732552. The AA and Asian SLE cases also demonstrated association at rs2732552 (p = 5 × 10-3, OR = 0.81 and p = 4.3 × 10-4, OR = 0.80, respectively). A meta-analysis of rs2732552 for all racial and ethnic groups studied produced pmeta = 2.36 × 10-13. This locus contains multiple regulatory sites that could potentially affect expression and functions of CD44, a cell-surface glycoprotein influencing immunologic, inflammatory, and oncologic phenotypes, or PDHX, a subunit of the pyruvate dehydrogenase complex. © 2011 The American Society of Human Genetics.